Peran Pendidikan Seni Budaya dalam Mengembangkan Karakter Siswa SDK ST. Yoseph Maumere - Benyamin Regi (Peneliti.net, 2021)
Education in the current era promotes character development in every subject. Educational institutions especially formal (early-upper middle age level) try to provide specific activities. This activity is expected to be able to support and encourage students to have good characterThis research is titled ‘Forming Student Character Based on Cultural Arts Education at SDK St. Yoseph Maumere. The problems in this study are (1) What is the strategy of cultural arts-based character education in SDK St. Yoseph Maumere, (2) What are the supporting and inhibiting factors for arts-based character education at the elementary school level?, (3) students, students, local education providers about the implementation and benefits of art and culture-based character education. The study was conducted at SDK St. Yoseph Maumere with consideration (1) SDK St. Yoseph Maumere was predicated as one of the schools active in the development of art and culture, (2) As an active school it turned out that it had many achievements both at the local and national level. The results of this research to show: (1) Art and cultural based character education in SDK St. Yoseph Maumere using habituation methods, (2) Schools have character education bases that are highlighted, (3) Cultural arts subjects have been implemented in character education, (4) Education characters are not exclusive in cultural arts lessons but throughoutsubjects.